2020
DOI: 10.21203/rs.3.rs-72766/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of Sheep Lice and Efficacy Evaluation of 60% Diazinon and 1% Ivermectin against Bovicola ovis in Sayint District, South Wollo, Ethiopia

Abstract: Background Sheep lice, caused by Bovicola ovis are very common in Ethiopia. It can result decreased production and reproduction, downgrading and rejection of skins in tannery industries. A cross-sectional and experimental study were conducted in Sayint District, South Wollo, Ethiopia which aims to determine the prevalence of sheep lice with the associated risk factors, identify the major sheep lice species and evaluate the efficacy of 60% Diazinon and 1% Ivermectin against Bovicola ovis. Study kebeles and ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, repeated evaluations of lice infestations in farmtreated animals confirmed this (Mckiernan et al, 2021). In Ethiopia, it has also been shown that B. ovis is resistant to 1% ivermectin (Legesse et al, 2020).…”
Section: Licementioning
confidence: 52%
“…In addition, repeated evaluations of lice infestations in farmtreated animals confirmed this (Mckiernan et al, 2021). In Ethiopia, it has also been shown that B. ovis is resistant to 1% ivermectin (Legesse et al, 2020).…”
Section: Licementioning
confidence: 52%